The Effect of Environmental Communication on Community Participation in Waste Management (Case Study of Emak.id Waste Bank, South Lampung, Indonesia) - Wulandari, Ayu; Hernawan, Wawan; Waskito, Budhi (Indonesian Journal Publisher, 2025)
This study aims to examine the effect of environmental communication on increasing community participation in waste management at Emak.id Waste Bank, Natar District, South Lampung Regency. The background of this study is the low level of public awareness and participation in sustainable waste management, despite various environmental communication efforts that have been carried out by waste bank organizers. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 97 respondents who are members of the Emak.id Waste Bank, which were selected using the Proportional Stratified Random Sampling technique. The independent variable is environmental communication measured through the dimensions of waste management socialization (X1), communication media used (X2), and waste transactions as education (X3), while the dependent variable is community participation (Y). Data were analyzed using multiple linear regression. The results showed that socialization, communication media, and waste transaction as education, both partially and simultaneously, had a positive and significant effect on community participation in waste management. The findings confirm that an integrated environmental communication strategy is essential increase community involvement in community-based waste management programs.